EGFR: A Master Piece in G1/S Phase Transition of Liver Regeneration - Alexandra Collin de l'Hortet; Hélène Gilgenkrantz; Jacques-Emmanuel Guidotti (International Journal of Hepatology)
Unraveling the molecular clues of liver proliferation has become conceivable thanks to the model of two-third hepatectomy. The synchronicity and the well-scheduled aspect of this process allow scientists to slowly decipher this mystery. During this phenomenon, quiescent hepatocytes of the remnant lobes are able to reenter into the cell cycle initiating the G1-S progression synchronously before completing the cell cycle. The major role played by this step of the cell cycle has been emphasized by loss-of-function studies showing a delay or a lack of coordination in the hepatocytes G1-S progression. Two growth factor receptors, c-Met and EGFR, tightly drive this transition. Due to the level of complexity surrounding EGFR signaling, involving numerous ligands, highly controlled regulations and multiple downstream pathways, we chose to focus on the EGFR pathway for this paper. We will first describe the EGFR pathway in its integrity and then address its essential role in the G1/S phase transition for hepatocyte proliferation. Recently, other levels of control have been discovered to monitor this pathway, which will lead us to discuss regulations of the EGFR pathway and highlight the potential effect of misregulations in pathologies.